2007
DOI: 10.1002/cncr.22871
|View full text |Cite
|
Sign up to set email alerts
|

Active surveillance for selected patients with renal masses

Abstract: BACKGROUND. The objective of the current study was to evaluate the outcome of a surveillance strategy in patients with renal masses. METHODS. The medical records of patients with renal masses diagnosed between January 1992 and May 2006 were reviewed retrospectively. In all, 45 patients with renal masses under observation were identified. Of these, 35 patients with 44 renal masses measuring <4 cm in dimension at the time of diagnosis and who were followed for at least 6 months were included in the review. Patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 128 publications
(37 citation statements)
references
References 19 publications
(24 reference statements)
0
34
0
3
Order By: Relevance
“…To address the possibility that contemporary NSS mortality rates could be lower, we varied this estimate substantially to determine the potential effects on our results. We found that below a rate of 1%, the NSS strategy would yield a slightly higher quality-adjusted life expectancy (38)(39)(40)(41)(42)(43)(44)(45)67 ). Furthermore, adequate data were not available to validate our model predictions for patients with biopsynegative RCC using an independent data source.…”
Section: Health Policy and Practice: Cost-effectiveness Analysis For mentioning
confidence: 95%
See 4 more Smart Citations
“…To address the possibility that contemporary NSS mortality rates could be lower, we varied this estimate substantially to determine the potential effects on our results. We found that below a rate of 1%, the NSS strategy would yield a slightly higher quality-adjusted life expectancy (38)(39)(40)(41)(42)(43)(44)(45)67 ). Furthermore, adequate data were not available to validate our model predictions for patients with biopsynegative RCC using an independent data source.…”
Section: Health Policy and Practice: Cost-effectiveness Analysis For mentioning
confidence: 95%
“…However, because practitioners have become more confi dent in renal mass biopsy results, fewer correlative surgical histologic results for biopsy-negative tumors are available ( 9,10,14,26,29,62 ), and the use of tumor indolence as a proxy for surgical confi rmation of benignity has increased. However, clinical follow-up of false-negative results does not prove tumor benignity, and the assumption that tumor indolence and benignity are equivalent may contribute to higher ( 38,41,44 ). † Although growth data were reported, the percentage of tumors that grew during follow-up was not reported; thus, data from this study could not be incorporated for this statistic.…”
Section: Biopsy Test Performance In the Modelmentioning
confidence: 99%
See 3 more Smart Citations